2013
DOI: 10.30638/eemj.2013.277
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effective Width of Riparian Buffers in Korean Watersheds Using the Swat Model

Abstract: Riparian buffers play an important role in improving water quality, providing wildlife habitat, and reducing suspended sediments and pollutants entering the water body. The efficiency of pollutant reduction by a riparian buffer is greatly influenced by the width of the riparian buffer. In this study, the Soil and Water Assessment Tool (SWAT) model was applied to the Yudeung Stream watershed, Daejeon Stream watershed, and Gap Stream watershed to determine the most effective width of the riparian buffer. These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…All 9 studies also contributed other types of evidence. Characteristics of woodland buffers enabling effective nutrient mitigation were revealed (Matteo et al, 2006;Moon et al, 2013;van Looy et al, 2013;Xu et al, 2021). Line et al (2002) observed beneficial effects from 9 to 15 m of riparian woodland.…”
Section: Effects Of Leaf Litter and Riparian Canopiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All 9 studies also contributed other types of evidence. Characteristics of woodland buffers enabling effective nutrient mitigation were revealed (Matteo et al, 2006;Moon et al, 2013;van Looy et al, 2013;Xu et al, 2021). Line et al (2002) observed beneficial effects from 9 to 15 m of riparian woodland.…”
Section: Effects Of Leaf Litter and Riparian Canopiesmentioning
confidence: 99%
“…Matteo et al (2006) predicted small levels of nutrient retention (3.5%-4%) in urban environments under 60 m riparian buffers. To achieve a 10% reduction in nutrient load, Moon et al (2013) used modeling to prescribe 70-80 m wide deciduous buffers but narrower (60-70 m) evergreen buffers. Significant positive effects on nutrient retention of the presence of forest within 200 m of urban stream channels were predicted (Xu et al, 2021).…”
Section: Effects Of Leaf Litter and Riparian Canopiesmentioning
confidence: 99%
“…Vegetasi merupakan salah satu faktor yang memengaruhi fungsi perlindungan sempadan sungai, selain air dan tanah/bentuk lahan (Swanson et al, 2017). Vegetasi mempunyai peran penting dalam mengurangi transfer sedimen dan polutan ke badan air sungai (Moon et al, 2013;Tiecher et al, 2017), memperkuat stabilitas tepian sungai (Krzeminska et al, 2019), meningkatkan kualitas air sungai (Chua et al, 2019), menurunkan suhu aliran (Wondzell et al, 2019), meningkatkan jumlah dan keanekaragaman spesies burung (Kontsiotis et al, 2019). Vegetasi tebing sungai dapat meredam kecepatan aliran air sungai dan memindahkan distribusi kecepatan ke tengah sungai (Maryono, 2015).…”
Section: Pendahuluanunclassified